Injuring by an advertisement: who will compensate a moral damage? (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In the article talked about psychological pressure of advertisement on a potential consumer, about advertisement motions that discredit advertisement activity; the question about responsibility of advertisers and the advertising profession before society raises.
Keywords: advertisement; advertisement legislation; advertisement appeal; psychological pressure; consumer